Assessing intrinsic capacity for person‐centred HIV care: a cross‐sectional study in ageing populations in Malaysia and Hong Kong - Reena Rajasuriar; Syaza Hisham; John Son Lim; Jean Yi Cheong; Wen Ying Ho; Siew Hwei Yap; Nurul Syuhada Zulhaimi; Malinee Neelamegam; Catherine Cheung; Vivian Wong; Ruhana Che Yusof; Kejal Hasmukharay; et al. (Journal of the International AIDS Society)
Abstract Introduction WHO's Integrated Care for Older People (ICOPE) proposes we measure the functional construct of intrinsic capacity (IC) to monitor and identify individuals with age‐associated vulnerabilities. Assessments of IC may be useful to address the evolving, non‐HV care needs of ageing people with HIV (PWH). However, to date, its utility within the context of HIV has not been assessed. Methods Participants included 200 PWH attending out‐patient care (2021−2023) in Universiti Malaya Medical Centre, Malaysia and 101 community controls aged 35 years and above. The ICOPE framework was adapted to derive aggregate IC scores (ranging 0–6) encompassing the five domains of cognition, sensory (hearing and vision), mobility, mood and vitality. Multivariable analyses were used to explore the association of IC scores in PWH with multiple health outcomes including frailty, difficulties performing instrumental activities of daily living (IADL) and inflammatory markers. Area under the receiver operator characteristic (AUC‐ROC) was calculated to predict frailty and IADL deficits in the current cohort and an independent cohort of 275 PWH from Hong Kong (HK). Results Median (interquartile range, IQR) age among PWH and controls were 50 (42−56) and 50 (39−59) years, respectively. There were more males among PWH (83% vs. 56%, p<0.001). All PWH received antiretroviral therapy (ART) for a median duration of 11 (8−14) years. Aggregate IC scores were lower in PWH but not significantly different compared to controls, (5.4 vs. 5.6, p = 0.093) and PWH performed significantly worse than controls only in the cognitive domain. Aggregate IC scores in PWH was independently associated with frailty (OR 0.17 95% CI 0.07−0.42, p<0.001), IADL deficits (OR 0.25 95% CI 0.14−0.46, p<0.001) and all other patient‐reported outcomes assessed. Aggregate IC scores correlated with IL‐6 but not sCD14 and sCD163 levels. IC scores performed well in identifying PWH with frailty (AUC‐ROC ≥ 0.80) in the HK and Malaysian cohorts but more modestly (AUC‐ROC ≥ 0.64) for IADL deficits. Conclusions IC is a good composite measure to monitor non‐HIV, age‐associated physical and social vulnerabilities in PWH on ART and should complement disease‐based monitoring in routine HIV care. Assessments of IC should be validated in larger, longitudinal cohorts of PWH from diverse settings.